Sanksi Pidana terhadap Pelaku Tindak Pidana Penipuan dalam Pencucian Uang Pada PT. Purnama Kertasindo Jakarta Timur - I Made Ngurah Adi Kusumadewa; I Nyoman Gede Sugiartha; I Made Minggu Widyantara (Warmadewa Press, 2022)
That fraud is listed in the Criminal Code (KUHP) Chapter XXV bedrog Article 378 which is an act that seeks self-profit by violating the law, using deceit, and using a series of lies. Meanwhile, money laundering is included in Law No. 8 of 2010 which means all actions related to placing objects of property originating from criminal acts. The problems are 1) What is the form of criminal sanctions against perpetrators of fraud in money laundering? And 2) What are the legal considerations of the panel of judges in making decisions against perpetrators of fraud in money laundering at PT. PURNAMA KERTASINDO EAST JAKARTA?. The method used is the normative method. Fraud has the aim of possessing property to benefit oneself in the form of money or objects in an illegal manner. This can cause a person to commit fraud which is usually the case and will also lead to other irregularities such as money laundering. Imprisonment sanctions are often used to punish deviant criminals.